2021
DOI: 10.7441/joc.2021.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes Towards New Circular Models in the Fashion Industry

Abstract: The fashion industry ranks among the most resource-intensive and environment-polluting industries. Circularity has been discussed as a solution to these problems. However, the transition towards a circular economy (CE) requires fundamental changes in the behavior and actions of all market entities. Consumer interest in sustainability and circularity can stimulate businesses to become more responsible and to offer circular solutions, and thus create a significant competitive advantage for these firms in a globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…Undoubtedly, consumers have become more environmentally aware and concerned, and the desire to change their attitudes is increasingly visible (Musova et al, 2021). Socially responsible consumers are those who perceive social and environmental issues as fundamental in the buying decision process and through their actions seek to have a good impact on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, consumers have become more environmentally aware and concerned, and the desire to change their attitudes is increasingly visible (Musova et al, 2021). Socially responsible consumers are those who perceive social and environmental issues as fundamental in the buying decision process and through their actions seek to have a good impact on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…One influential theoretical framework to approach the social media-user interactions is the uses and gratifications theory (U&G), which highlights the importance of individuals' social and psychological needs in shaping their motivations and, consequently, their communicative behaviors (Katz et al, 1973 ; Rubin, 1994 ; Papacharissi and Rubin, 2000 ; Abbas and Mesch, 2015 ). On one hand, previous studies indicated that Gen-Zs differ from their predecessors in many aspects of online motivations, such as being more desired for self-expressing and self-disclosing, online shopping, online enjoyment, memetic engagements, content-generating, and sustainable online behaviors (Hargittai, 2010 ; Turner, 2015 ; PrakashYadav and Rai, 2017 ; Dabija and Lung, 2018 ; Dabija and Bǎbuţ, 2019 ; Viţelar, 2019 ; Andronie et al, 2021 ; Hu and Cheong, 2021 ; Musova et al, 2021 ; Vǎtǎmǎnescu et al, 2021 ). On the other hand, the extent to which social media uses can satisfy Gen-Zs' online motivations depends on their affordances.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Valaskova et al (2021) found in a study on the changes in consumers’ purchase patterns as a consequence of the COVID-19 pandemic that services will become one of the decisive factors for consumers’ purchase behavior. Musova et al (2021) also proposed that if businesses react to consumer expectations regarding circularity by offering products and services with environmental benefits may increase their competitiveness. Furthermore, studies on online lending have also proved that convenience is the main selling point of online lending platforms.…”
Section: Literature Review Research Model and Hypothesesmentioning
confidence: 99%